Comparative analysis of secondary education in India and higher medical education in Ukraine taking into account the Bologna system. - O. Yu. Pototskaya; K. M. Shevchenko; D. G. Marchenko; S. B. Morozova; L. A. Filimonova (Морфологія, 2016)
Background. Transition from one system of education to another results in a conflict between two methodological algorithms. This conflict is more sharp for students, who change countries during educational process. Among all the 62000 of foreign students who study in Ukraine Indians occupy the third place. Objective. The purpose of this work was to compare Indian system of school education with Ukrainian system of high medical education. Methods. To achieve this aim, official websites, interviews with teachers and students and also questionnaire survey were used. Results. The most prominent differences include, first of all, the source of information: in Indian schools it is teacher explanation, in Ukrainian academy it is self-work. The second position is the frequency of examination: in Ukraine the most wide-spread forms are oral questioning and tests, while in India predominant form of examination is written, among which written questions are most widely used. Conclusion. Taken together our data suggests that teachers of the first courses should concentrate attention of the Indian students on the above mentioned differences between our system of education and Indian of education to facilitate their adaptation.